Density and diversity of birds in the wetlands of Yankari Game Reserve Bauchi Nigeria - Omotoriogun, Taiwo Crossby; Onoja, Joseph Daniel; Tende, Talatu; Manu, Shiiwua; Ottosson, Ulf (Journal of Wetlands Ecology, 2011)
The biological, chemical, and physical operations and attributes of wetlands are vital in facilitating food resources, water, and shelter, which many terrestrial bird and waterbird species rely on for their daily requirments. Wetlands in Yankari Game Reserve, Nigeria are key stone ecosystem that provides a stopover, breeding and/or foraging platform for migratory and resident birds. This study determined the density and diversity of birds in the wetlands of Yankari Game Reserve. Ten wetlands within the reserve were identified and surveyed. The sizes (kilometer square) and isolation distances (kilometer) of the wetlands were measured (using GPS and Map Source) to determine their effects on bird density and diversity. Point count survey method was used to count birds. One hundred and twenty three species of birds belonging to 51 families were recorded in the wetlands. Significant patterns in the densities of birds were observed across the wetlands (Kruskal-Wallis H, X2=167.116, P=0.001) and also sizes of wetlands (Wilcoxon test: Z= -2.803, P=0.005). There was differences in mean number of birds in survey time (Kruskal-Wallis, X2=15.784, P=0.045). Evenings were probably most preferred in bird-wetland utilization. Key words: Density; Diversity; Yankari ecosystem; Wetland utilization DOI: http://dx.doi.org/10.3126/jowe.v5i0.4778 J Wet Eco 2011 (5): 48-58